Engineer and Feminist: Elsie Gregory MacGill and the Royal Commission on the Status of Women, 1967-1970 - Sissons, Crystal (Scientia Canadensis, 2006)
AbstractCan a woman engineer by a feminist? This article argues in the affirmative using a case study of Elsie Gregory MacGill. Elsie Gregory MacGill was Canada's first woman electrical engineer, graduating in 1927 from The University of Toronto. She then became the first woman to earn a degree in aeronautical engineering from the University of Michigan in 1929. While establishing herself in a predominantly masculine profession, MacGill, also a third generation feminist, actively worked for women's equal rights and opportunities in Canadian society. A case study of her role in the Royal Commission of the Status of Women (RCSW), 1967-1970, is used to illustrate that not only can a woman engineering be a feminist, but more importantly that her dual background allowed her to effectively bridge the worlds of the engineering and feminism in engineering the RCSW.